Problem-Based Learning in Multimodal Learning Environments Learners’ Technology Adoption Experiences - Ioannou, Andri; Vasiliou, Christina; Zaphiris, Panayiotis (My University, 2016)
In this study, we enhanced a problem-based learning (PBL) environment with affordable, everyday technologies that can be found in most university classrooms (e.g., projectors, tablets, students’ own smartphones, traditional paper–pencil, and Facebook). The study was conducted over a 3-year period, with 60 postgraduate learners in a human–computer interaction course, following a PBL approach to teaching and learning. First, this article contributes a detailed description of how PBL can be enacted in a multimodal, technology-rich classroom. Second, the study presents evaluation data on learners’ technology adoption experience while engaging in PBL. Overall, the participants positively endorsed the learning environment, rating their experience highly on scales of communication and interaction, reflection, perceived learning, and satisfaction. In addition, quantitative content analysis of Facebook use documented how the physical and digital tools in the environment, coupled with the capability of Facebook as a recordkeeping and communication tool, were integral part of the PBL process.
Keywords: Multimodal learning environment; Problem-based learning; PBL; Technology-enhanced PBL; Computer-supported PBL; Facebook; Technology adoption; Learner experience; Educational technology; HCI education